Analysis of Mechanical Properties for Al-MMC Fabricated through an Optimized Stir Casting Process. (29th March 2022) - Gugulothu, Bhiksha; Nagarajan, N.; Pradeep, A.; Saravanan, G.; Vijayakumar, S.; Rao, Janardhana
Abstract : This work concentrated on preparation of Al-based composites through stir casting process. Al6082 was chosen as base material that is reinforced with zirconium silicate and titanium carbide. As per Taguchi design L16 orthogonal array, specimens are produced with variation of casting parameters for performing tensile and hardness test. In this process, ZrSiO₄ is kept constant to 10 wt%, whereas TiC concentration varied from 2.5 to 10wt%. For analyzing the properties of optimized stir cast samples for AA6082/ZrSiO4/TiC, three input variables with four levels are taken such as Stir speed (SS) 300-750 rpm, Stir time (ST) 5-20 min, and Reinforcement (RI) 2.5-10 wt%. The Taguchi technique was used as an analyzer to determine optimal parameter on Tensile Strength (TS) and Hardness (HN). The Minitab-17 software is assisting to find analysis of variance (ANOVA), regression equation, and contour plots of the selected parameters. Finally, it is witnessed that SS (65.9%) is the maximum influenced factor that increases TS, followed by RI (23.1%) and ST (11%). The best combinations of parameters on TS and HN were found at SS2-ST1-RI2 (450 rpm, 5 min, and 5wt%) and SS3-ST2-RI4 (600 rpm, 10 min, and 10wt percent), respectively. From the contour plots, the casting variables SS (600-650 Rpm), ST (15-17.5 min), and RI (5-8 wt%) were proposed for achieving excellent mechanical properties.